Case Report: The acute appendicitis and incarcerated umbilical hernia: a rare association - Corbi, Letizia; Frediani, Simone; Aloi, Ivan Pietro; Bertocchini, Arianna; Accinni, Antonella; Pardi, Valerio; Inserra, Alessandro (Frontiers in Pediatrics, 2024)
Introduction: One of the most prevalent congenital wall abnormalities in children, umbilical hernias are often linked to premature or small-for-gestational-age babies. In cases of intestinal malrotation or if the cecum is very movable, generalized peritonitis may facilitate the imprisonment of these hernias. Case report: We described a case of a 4-month-old baby who had a prior reducible umbilical hernia with a history of fever, vomiting, poor appetite, and constipation for around 48 hours. The patient experienced significant intestinal bloating, vomiting, irreducibility of the umbilical hernia, skin pigmentation, and erythema at the umbilical site within two days after hospitalization. When there was no free abdominal air, a direct abdominal X-ray revealed evidence of hydro-gas stasis and various hydro-aerial levels that were pertinent to the ileum. In order to reduce the hernia, the patient had an emergency surgical treatment where the hernia sac was isolated and released from the ileal loop, which was securely attached to a fibrin plate. When the herniary sac was opened, a gangrenous and perforated appendix was found inside. On the seventh postoperative day, the patient was released from the hospital after an uncomplicated postoperative stay. Conclusion: Our patient's clinical presentation is similar to that of only one other case report involving a 25-day-old male patient. Our case presented with a variant of the clinical symptoms of the previously described umbilical hernia, which became unfixable and strangulated as a result of appendix inflammation. The appendix was discovered inside the hernia sac during surgery.